2020
DOI: 10.21203/rs.2.24037/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated sRNAome and RNA-Seq Analysis Reveals miRNA Effects on Betalain Biosynthesis in Pitaya

Abstract: Background: MicroRNAs (miRNAs) and their regulatory functions in anthocyanin, carotenoid, and chlorophyll accumulation have been extensively characterized in many plant species. However, the miRNA regulatory mechanism in betalain biosynthesis remains mostly unknown. Results: In this study, 126 conserved miRNAs and 41 novel miRNAs were first isolated from Hylocereus monacanthus, among which 95 conserved miRNAs belonged to 53 miRNA families. 34 candidate miRNAs related to betalain biosynthesis were differentiall… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…The proportion of miRNA of 24 nt (48.33%) was much higher than that of 21 nt (14.84%). This result is consistent with the length distribution of miRNA in pitaya ( H. monacanthus ) (Chen et al, 2020) and kiwifruit ( A. arguta ) (Li et al, 2019) but not in passion fruit ( Passiflora edulis ) (Paul et al, 2020). The results showed that the miRNAs of different plants differed in the distribution of their lengths.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The proportion of miRNA of 24 nt (48.33%) was much higher than that of 21 nt (14.84%). This result is consistent with the length distribution of miRNA in pitaya ( H. monacanthus ) (Chen et al, 2020) and kiwifruit ( A. arguta ) (Li et al, 2019) but not in passion fruit ( Passiflora edulis ) (Paul et al, 2020). The results showed that the miRNAs of different plants differed in the distribution of their lengths.…”
Section: Discussionsupporting
confidence: 85%
“…Many of them are widely involved in the plant growth and development, metabolism, hormone regulation, and various biological and abiotic stresses (Li et al, 2020). Presently, miR828, miR858, miR156, miR159, miR157, miR160, miR172, miR393, miR396, miR824, and miR870 in Litchi chinensis (Liu et al, 2017), Punica granatum (Saminathan et al, 2016), Hylocereus monacanthus (Chen et al, 2020), Raphanus sativus (Gao et al, 2019), Lycium ruthenicum (Qi et al, 2020), Diospyros kaki (Luo et al, 2015), Vaccinium ashei (Li et al, 2018), Actinidia arguta (Li et al, 2019), and Lonicera edulis (Li et al, 2018), respectively, have been found to be involved in the regulation of anthocyanin metabolism. Both miR156h‐3p and miR396a‐3p can target UFGT in L. edulis and significantly negatively correlate with anthocyanin biosynthesis (Cui et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The length distribution of the unique small RNA reads indicated that 24 nt were the most abundant (36.6%) (Supplementary Table 3B). Further, 47 unique conserved miRNAs and 415 novel miRNAs were identified, with lengths varied from 19 to 25 nt (Supplementary Figures 5A,B), which agreed with many other RNA-Seq experiments (Chen et al, 2020;Li et al, 2021). Of these miRNAs, 451 pre-miRNAs corresponding to 462 mature miRNAs were identified, which were grouped into 93 families (Supplementary Figure 5C and Supplementary Table 3C).…”
Section: Expression Profiles and Targets Of Small Ribonucleic Acids I...supporting
confidence: 84%
“…Transcriptomic research has been conducted on S. megalanthus, S. costaricensis and S. monacanthus to address a number of physiological processes. For instance, transcriptomic research has investigated the effect of lighting at night, the trypsin effect in fruit storage ( Pang et al, 2020 ), the response of roots to salt stress ( Nong et al, 2019 ), the response of plants to cold stress ( Zhou et al, 2020 ), and to characterize metabolic pathways in betalain biosynthesis in fruits ( Quingzhu et al, 2016 ; Cheng et al, 2020 ; Li et al, 2020 ; Hie et al 2020 ). Recently, for S. undatus , a chromosome level genome found genome duplication of betacyanin biosynthetic genes ( Zheng et al, 2021 ).…”
Section: Importance and Conclusionmentioning
confidence: 99%
“…Transcriptomic characterization along with comparative genomics has brought about a revolution in the study of the processes involved in management and domestication in plants and animals (see review by Barrera-Redondo, Piñero & Eguiarte (2020) ). Transcriptome research has been carried out in Selenicereus megalanthus, S. monacanthus and S. costaricensis to understand the effect of lighting at night on flowering, the effect of trypsin during storage of fruits ( Pang et al, 2020 ), the response of roots to salt stress ( Nong et al, 2019 ) and the response of plants to cold stress ( Zhou et al, 2020 ) in addition to characterizing the metabolic pathways in betalain biosynthesis in fruits ( Quingzhu et al, 2016 ; Cheng et al, 2020 ; Li et al, 2020 ; Hie et al, 2020 ; Zhang et al, 2021 ). Moreover, only a few genomes of species in Cactaceae have been assembled; in the case of S. undatus chromosome-scale or plastid genomes were based on cultivars from China such like “Yunnan” and “Guanhuabai” ( Chen et al, 2021 ; Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%